English Self-Efficacy in a Faith-Based Multilingual Boarding School: A Qualitative Case Study from Indonesia - Salsabila, Januba Roudloh; Sumardi, Sumardi; Putra, Kristian Adi (FOSTER: Journal of English Language Teaching, 2026)
This study examines students’ English self-efficacy in an Indonesian Islamic multilingual boarding school where English, Arabic, and Indonesian are used in daily and academic interactions. Using a qualitative case study approach, data were gathered through semi-structured interviews and non-participant observations involving three purposively selected students. The findings reveal that students’ English self-efficacy is shaped by internal factors, including intrinsic motivation and personal aspirations, as well as external influences such as peer support, school programs, and limited family involvement. Students demonstrated higher confidence in informal communication but showed hesitation in formal academic contexts due to concerns about linguistic accuracy and evaluation. The school’s multilingual environment through sustained language exposure, structured vocabulary practices, and peer-led activities was found to reinforce all four sources of self-efficacy proposed by Bandura: mastery experience, vicarious experience, social persuasion, and physiological and emotional states. Despite initial challenges such as linguistic overload and adaptation difficulties, continuous engagement in the multilingual setting fostered students’ resilience and confidence over time. This study contributes theoretically by illustrating how Bandura’s self-efficacy framework operates within a faith-based multilingual boarding school context and offers practical implications for strengthening English learning in similar educational environments.